Epiretinal Membrane Is Associated with Diabetic Retinopathy Severity and Cumulative Anti-VEGF Injections - Kakihara, Shinji; AbdelSalam, Mohamed; Zhuang, Kallista; Fawzi, Amani A. (Ophthalmology science (Online), 2025)
To identify and assess the risk factors for epiretinal membrane (ERM) formation in patients with diabetes mellitus (DM). A cross-sectional observational study. Diabetes mellitus subjects with varying severities of diabetic retinopathy (DR). Epiretinal membrane severity was graded using OCT macular volumetric scans. After comparing the features of eyes with and without ERM, a logistic regression model was employed to investigate risk factors for the presence of ERM formation, with explanatory variables that were statistically significant between 2 groups. The risk factors for ERM formation and their odds ratios. The study analyzed 207 eyes of 207 patients without center-involving diabetic macular edema, including 44 with DM but no DR, 23 with mild DR, 42 with moderate DR, 28 with severe nonproliferative DR, and 70 with proliferative DR. Among these, 49 eyes had ERM. Eyes with ERM demonstrated significantly higher DR severity, more frequent history of cataract surgery, a greater number of anti-VEGF injections, less frequent hypertension, and higher geometric perfusion deficits in the deep capillary plexus, as calculated by OCT angiography, compared to eyes without ERM. After adjusting for explanatory variables, the logistic regression model identified DR severity and the number of injections as significant risk factors for ERM formation. The adjusted odds ratios were 2.388 (95% confidence interval [CI]: 1.694–3.566, P < 0.0001) for DR severity and 1.196 (95% CI: 1.013–1.444, P = 0.0449) for the number of injections, respectively. In this cross-sectional study, DR severity as well as the number of anti-VEGF injections were identified as significant risk factors for ERM formation. Proprietary or commercial disclosure may be found in the Footnotes and Disclosures at the end of this article.